2010
DOI: 10.1037/a0019245
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of insight for long-term improvements in psychodynamic therapy.

Abstract: Insight seems to be a key mechanism of change in dynamic psychotherapy. Our results bridge the gap between clinical theory and empirical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 55 publications
7
90
0
2
Order By: Relevance
“…In addition, a recent experimental study of psychodynamic psychotherapy with and without moderate levels of transference interpretations (Hoglend et al 2006) failed to find differences in outcome between the low transference interpretation and moderate transference interpretation groups. However, they did find that some patient variables moderated the relationship between interpretation and outcome, and subsequent analysis has suggested that, as would be expected by theory, insight mediated the effect of transference interpretations on outcome (Johansson et al 2010). This finding suggests that interpretations are not always beneficial (so just doing more is not recommended), but when they are used in an appropriate context (and/or with attunement to the client's needs), they can be helpful.…”
Section: Unique Factorsmentioning
confidence: 59%
“…In addition, a recent experimental study of psychodynamic psychotherapy with and without moderate levels of transference interpretations (Hoglend et al 2006) failed to find differences in outcome between the low transference interpretation and moderate transference interpretation groups. However, they did find that some patient variables moderated the relationship between interpretation and outcome, and subsequent analysis has suggested that, as would be expected by theory, insight mediated the effect of transference interpretations on outcome (Johansson et al 2010). This finding suggests that interpretations are not always beneficial (so just doing more is not recommended), but when they are used in an appropriate context (and/or with attunement to the client's needs), they can be helpful.…”
Section: Unique Factorsmentioning
confidence: 59%
“…However, we think that this is a reasonable approximation, comprising some clear core features of negative counter-transference, but acknowledge that we have not included all possibilities. While the magnitudes of the above relationships and effects are medium to large in this sample, formal mediational analyses (e.g., like Johansson et al, 2010) must await a larger replication.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that a follow-up time frame of 5 years might be required. Future studies could also include naturalistic ratings of the therapy process within the context of randomized comparative treatment trials, such as recently reported by the FEST study (Johansson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, improvement in another important dynamic therapy mechanism measure, namely reflective functioning, has been found to be associated with outcome of dynamic therapy for major depressive disorder (Bressi et al 2017) and borderline personality disorder (De Meulemeester et al 2017;Fischer-Kern et al 2015). Although full mediational analyses documenting change in the mechanism measure (i.e., the mediator) predicting subsequent outcome are rare for any psychotherapy, at least three studies have found that change in a dynamic mechanism measure (insight) predicts subsequent outcome of PDT (Connolly Gibbons et al 2009;Johansson et al 2010;Kallestad et al 2010). Thus, biases or "myths" towards PDT (Abbass et al 2017) are refuted by empirical data.…”
Section: Discussionmentioning
confidence: 99%